ENHANCING MATHEMATICAL CREATIVE THINKING ABILITY: EXPERIMENTATION WITH REALISTIC MATHEMATICS EDUCATION BY EMBEDDING ICE BREAKING IN JUNIOR HIGH SCHOOL - Sury Adellia Ramadhanta; Rustam Effendy Simamora; Dwi Susanti (EDU-MAT: Jurnal Pendidikan Matematika, 2024)
The effectiveness of Realistic Mathematics Education (RME) in improving students' mathematical abilities has been examined through various research. Meanwhile, the use of ice-breaking (Ib), considered by experts and educational researchers as a highly beneficial tactic for improving learning effectiveness, had yet to be fully explored in the context of integration with RME. The study aimed to examine the effectiveness of Ib-RME (RME integrating Ib) in enhancing students' mathematical creative thinking abilities (MCTA) at SMPN 14 Tarakan, Indonesia. Involving 64 seventh-grade students in a quasi-experimental design, the experimental group adopted the Ib-RME approach. In contrast, the control group followed the conventional teaching method employed by mathematics teachers in the class, including ice-breaking activities as normally implemented in the classroom setting. Data analysis using t-tests revealed a significant improvement in MCTA in the Ib-RME group, confirming the effectiveness of this approach. The research noted that conventional teaching also enhanced MCTA, although to a lesser extent than Ib-RME. These findings contributed to understanding the potential integration between RME and Ib in improving Mathematics learning outcomes, particularly in developing MCTA. The implications could serve as a basis for the development of innovative and effective teaching approaches in the mathematics education. Keywords: conventional learning, ice-breaking, mathematical creative thinking ability, realistic mathematics education, school mathematics.